Zhi-zi-chi decoction exerts hypnotic effect through gut-brain axis modulation in insomnia mice - Wang, Qianqian; Zhang, Boyi; Guo, Zixuan; Huang, Jiawei; Niu, Yuanyuan; Huang, Junhong; Huang, Yu; Guo, Dandan; Wang, Baiyan; Feng, Shuying (Frontiers in Microbiology, 2025)
BackgroundInsomnia, a frequently encountered sleep disorder, boasts a high prevalence rate on a global scale. Currently, Western medications are widely used for its treatment; however, they may cause adverse effects such as dependence and daytime drowsiness. Traditional Chinese medicine (TCM) offers a safer alternative. Zhi-zi-chi Decoction (ZZCD), composed of Fructus gardeniae and fermented soybean, has shown potential in promoting sleep, but its mechanism remains unclear.MethodsA PCPA-induced mice model of insomnia was used to evaluate the therapeutic effects of ZZCD. Behavioral tests, neurotransmitter assays, ELISA for HPA axis and inflammatory markers, 16S rDNA gut microbiota sequencing, and histological analyses of brain and colon tissues were performed.ResultsZZCD significantly improved sleep and reduced anxiety-like behavior. It restored GABA and 5-HT levels while lowering GLU and DA, normalized HPA axis activity, reduced inflammatory cytokines, and increased beneficial gut bacteria such as Ligilactobacillus. Histology confirmed neuroprotective and gut barrier-enhancing effects.ConclusionZZCD alleviates insomnia by modulating the gut-brain axis, rebalancing neurotransmitters, and restoring microbial homeostasis. These findings support its use as a safe and effective treatment for insomnia.